Influence of lime and fertilizers upon the mineralization of peat nitrogen in incubation experiments - Armi Kaila; Sylvi Soini; Erkki Kivinen (Scientific Agricultural Society of Finland, 1954)
An attempt has been made to elucidate the influence of lime and fertilizers upon the mineralization of peat nitrogen under laboratory conditions. The main object was to study differences between the responce of various kinds of peats to these treatments and to the incubation under conditions favourable for the activity of microorganisms. The material consisted of eight peat samples from North Finland. Four of them were fen peats with a virgin productivity of 6—8. The other four originated from untillable bogs with a virgin productivity of 1—3. All the samples were from virgin peat lands and only slightly decomposed. In spite of the different origins of these peat groups no marked differences in their chemical composition and characteristics could be found. This was supposed to be due to their low degree of decomposition. In the first large incubation experiment carried out at 15°—22 °C the accumulation of nitrate-nitrogen during the B—lo8—10 months of incubation was relatively high in all the limed samples, but marked nitrification occurred also in most of the un-limed samples, the Sphagnum fuscum peat being the most prominent exception. On the average, the effect of lime upon the total accumulation of mineral nitrogen was positive only in three of the fen peats and in the Sphagnum fuscum sample. In the second experiment lime seemed to stimulate the ammonification in the Sphagnum peats during the first month of incubation, but later on the accumulation of mineral nitrogen was found to be almost equally intensive in the limed and un-limed samples. No significant effect of potassium, phosphorus and nitrogen fertilizers could be stated in the incubation experiments. The same was true in respect to the effect of copper sulphate, zinc chloride or ammonium molybdate. The influence of ash upon the changes in the mineral nitrogen content of one fen peat was supposed to be due to its neutralizing agencies. The accumulation of mineral nitrogen, particularly of ammonium nitrogen, was highest in the untreated samples. ...